OPTIMIZING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT THROUGH E-LEARNING METHOD WITH WHATSAPP APPLICATION - Yustira Kharlina Tangiduk; Nurmin Samola; Rinny Rorimpandey (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This study aims to determine whether the E-learning method can be effective in optimizing students' reading comprehension of descriptive text with WhatsApp Application. This research was conducted in class X MIA 1 SMA Negeri 1 Buko in the academic year of 2020/2021. This study used one group-pretest-postest design of research with the data analysis were the frequency distribution of scores, mean and standard deviation. The questions from the pretest and posttest used the type of multiple choice questions with questions about the descriptive text. From this result, it was found that the mean of posttest Y = 7.8 with standard deviation Sy = 0.79 was higher than mean score at pretest X = 5.33 with standard deviation Sx = 0.89. It means that students' reading comprehension in descriptive text was higher after treatment at posttest than pretest. So the researcher concluded that the application of the E-learning method through WhatsApp application was effective in optimizing students' reading comprehension of descriptive text. Keywords: Optimizing, Descriptive Text, E-learning Method.